Brucellosis in children in Bosnia and Herzegovina in the period 2000 - 2013 - Sead Ahmetagić; Humera Porobić-Jahić; Nada Koluder; Lejla Čalkić; Snježana Mehanić; Eldira Hadžić; Nevzeta Ibrahimpašić; Svjetlana Grgić; Mirela Zirić; Jelena Bajić; Denis Žepić (Medicinski glasnik, 2015)
Aim: To analyse clinical, laboratory and epidemiological characteristics of brucellosis in children in Bosnia and Herzegovina. Methods: The study included 246 children aged 0-18 years, who were hospitalized in Clinics and Departments for Infectious Diseases in Tuzla, Sarajevo, Banja Luka, Zenica and Bihać in the period 2000-2013, in whom the diagnosis of brucellosis was established based on anamnestic data, clinical features and positive results from blood culture and/or positive results from one of the serological tests. Results: In this period, a total of 2630 patients, 246 (9.35%) of whom were children, were treated from brucellosis at the Clinics and Departments in Bosnia and Herzegovina. In the majority of cases, the children were from rural parts of the country, 226 (91.87%);214 (87.04%) cases had direct contact with sick animals, sick family member or consumption of unpasteurized dairy products from farms where brucellosis had been already established. Male children predominated, 157 (63.82%). The most frequent clinical features in affected children were fever, 194 (78.86%) and joint pain, 158 (64.22%). The average duration of antimicrobial treatment was 42.85 ± 10.67 days. A total of 228 (92.68%) children were completely cured, while relapses occurred in 18 (7.32%) children. Conclusion: Since brucellosis is an endemic disease in Bosnia and Herzegovina, it is important that physicians in their daily practice consider brucellosis and establish proper diagnosis and therapy in children with prolonged fever, arthralgia, leukopenia and positive epidemiological data, especially in rural parts of the country.
Keywords: clinical features; epidemiological characteristics; diagnosis; treatment